Mengembangkan Budaya Mutu Sekolah melalui Kepemimpinan Transformasional di SD Negeri 3 Pengkelak Mas - Muhammad, H. (ARZUSIN, 2022)
The development of the quality culture in schools is carried out through the development of innovative learning programs, the development of extracurricular activities, the development of the students' culture and character, and the development of academic and non-academic achievement. The obstacles faced by teachers in implementing the culture quality improvement program are the incomplete understanding of the implementation of the 2013 curriculum. The solution to overcome this matter is that the principal applies transformational leadership with a mentoring approach to the teacher when performing his duties in the classroom. The principal's approach through management approach includes: First, the planning stage by determining the quality target, disseminating the quality target to the school community. Second, the organizing stage involves the establishment of an organizational structure, the delivery of tupoksi, and the delegation of authority. Third, the leadership stages include training teachers, assisting teachers and employees, monitoring teachers in the classroom, motivating, discussing findings, focusing on quality targets and follow-up. Fourth, the monitoring and evaluation stage includes: school programs evaluation. The impact of this action is: First, the original learning process of teacher-centered learning with lecture method turned into a more innovative student-centered learning (PAKEM) with an integrated thematic approach to the scientific model, using various media in the classroom and outside the classroom as well utilizing resource persons from community leaders / DUDI. Second, the initial assessment of the knowledge aspect only changes to an authentic assessment by assessing aspects of attitude, knowledge and skills. Second, the initial assessment of the knowledge aspect only changes to an authentic assessment by assessing aspects of attitude, knowledge and skills. Thirdly, the extracurricular development increased, initially, it was only the scouts, but today the other activities are including music, independent garbage management (PSM), Hadroh Art, Vocal, English, Art, Batik, ICT, Qiroati. Fourth, the development of attitude and character has been entrusted, i.e. religious, discipline, environmental care, and achievement. Fifth, academic and non-academic achievement increased from the district-level championship increased until DIY level and even into national level.